PERSPECTIVES OF EFFICIENCY OF STEEL POURING AND INCREASE OF STEEL INGOT QUALITY - E. I. Marukovich; V. Ju. Stetsenko; V. A. Matochkin (Литьë и металлургия)
Jet crystallizer, device of flooded-stream secondary cooling, structural- superfine silumin modifier are developed in respect to plant technology of steel pouring. They allow to increase productivity of the process and to increase the steel ingot quality.